HOTTIP Predicts Poor Survival in Gastric Cancer Patients and Contributes to Cisplatin Resistance by Sponging miR-216a-5p - Zhao, Rui; Zhang, Xin; Zhang, Yanli; Zhang, Yaping; Yang, Yongmei; Sun, Yue; Zheng, Xin; Qu, Ailin; Umwali, Yvette; Zhang, Yi (Frontiers in Cell and Developmental Biology, 2020)
Gastric cancer (GC) is a significant public health burden worldwide, and cisplatin resistance is the leading cause for the failure of chemotherapy in this disease. Previous studies have revealed that HOXA transcript at the distal tip (HOTTIP) is involved in the pathology of GC and is associated with poor overall survival. However, the functional role of HOTTIP in GC chemoresistance remains unclear. In this study, quantitative real-time PCR was used to analyze HOTTIP expression in GC cell lines and in tissues of GC patients who received cisplatin-based chemotherapy. The mechanism of HOTTIP-mediated chemoresistance was assessed using cell viability, apoptosis, and autophagy assays. The relationships among HOTTIP, miR-216a-5p, and Bcl-2 were determined using luciferase reporter and western blot assays. HOTTIP was markedly upregulated in the tissues of GC patients who were treated with gastrectomy and cisplatin chemotherapy, especially in those with recurrent tumors. Further, HOTTIP was increased in the cisplatin-resistant cell line, SGC7901/DDP, compared to the parental cells, SGC7901. Functional assays demonstrated that HOTTIP expression promoted cisplatin resistance and inhibited apoptosis and autophagy in GC cells. Mechanistic investigations revealed that HOTTIP may regulate the functions of GC cells by sponging miR-216a-5p. MiR-216a-5p overexpression decreased Bcl-2 expression, enhanced Beclin1 expression, and active autophagy. Taken together, our study demonstrated that HOTTIP is closely associated with recurrence in GC patients. HOTTIP expression confers cisplatin resistance by regulating the miR-216a-5p/BCL-2/Beclin1/autophagy pathway, which provides a novel strategy to overcome resistance to chemotherapy in GC.